Recommendations for care and attention of premature newborn in times of COVID-19 pandemic: Integrated Literature Review - Florindo, Adriana Matos Ferraz; Gavasso, Giovanna Campos; Lopes, Jaqueline Pereira; De Oliveira Gomes Vieira, Júlia; De Melo, Rafael; Dos Santos, Gustavo Gonçalves [UNESP]; Frazão, Zaide Silva (Sociedad de Obstetricia y Ginecologia de Venezuela, 2021)
Objective: To describe recommendations for the care and handling of preterm infants in the COVID-19 pandemic scenario. Methods: Integrated Literature Review (ILR) conducted in 2020 in databases in the Virtual Health Library (VHL) by extracting scientific productions from the databases: MEDLINE, SCIELO, PUBMED and LILACS, with a final sample of 14 publications. Results: Among the recommendations found in the studies analyzed, regarding childbirth, it is recommended to choose the best time, route and place, prioritizing the use of a negative pressure room. After delivery, newborns should have the umbilical cord clamped, be cleaned and dried as soon as possible, and isolated and tested early. After initial care, the use of a mask and hand hygiene is recommended before each meal or other close contact with the newborn. Ideally, suspected or contaminated RN should be kept in isolation and constantly monitored, with a quarantine period of at least 14 days. Conclusions: The knowledge of nurses and other health care professionals about prevention and control measures for newborn infection with COVID-19 is critical to the prevention, control, and reduction of the impact of the pandemic on the neonatal population.
Recomendaciones para el cuidado y la atención de los recién nacidos prematuros en tiempos de la pandemia de COVID-19: Revisión integrada de la literatura
Keywords: Coronavirus infections; COVID-19; Neonatal Nursing and Premature Birth Infections; Nursing Care